Influence of neoadjuvant chemotherapy on prognosis of patients with synovial sarcoma - Yanan Wu (World Journal of Surgical Oncology, 2017)
Abstract Background This study aimed to explore the clinical efficacy of neoadjuvant chemotherapy combined with surgery in primary synovial sarcoma of the limbs and trunk through retrospective analysis of patients with primary synovial sarcoma of the limbs and trunk treated by this treatment in our hospital. Methods A total of 89 patients diagnosed with synovial sarcoma were enrolled in this study between January 2005 and December 2011 in PLA General Hospital. Most of the patients received neoadjuvant chemotherapy combined with operative treatment (84.3%), 10.1% of them received adjuvant chemotherapy combined with operative treatment, and only 5.6% received merely operative treatment. The influence on the prognosis of patients with synovial sarcoma was analyzed by the statistics overall survival (OS), progression-free survival (PFS), local control (LC), and freedom from distant metastasis (FFDM). Results The median follow-up time was 68.6 months. The 5-year OS, 5-year PFS, 5-year LC, and 5-year FFDM of the patients were 80.2, 60.5, 78.8, and 80.8%, respectively. The OS of the patients with a tumor size >5 cm was lower (91.4 vs 73.1%, P < 0.05). Besides, the OS and FFDM of neoadjuvant chemotherapy were better than those of adjuvant chemotherapy (84.5 vs 55.6%, P = 0.015, and 83.8 vs 55.6%, P = 0.028, respectively). However, there was no significant difference in the LC and PFS. Conclusions Neoadjuvant chemotherapy was beneficial for patients with synovial sarcoma, and it could improve survival time and control distant metastasis. Tumor size was an important factor influencing patients’ prognosis.